Development of a novel Haemabiome tool for the high-throughput analysis of haemopathogen species co-infections in African livestock - Yalcindag, Erhan; Vasoya, Deepali; Hemmink, Johanneke D.; Karani, Benedict; Hernandez Castro, Luis Enrique; Callaby, Rebecca; Mazeri, Stella; Paxton, Edith; Connelley, Timothy K.; Toye, Phil; Morrison, Liam J.; Bronsvoort, Barend Mark de C. (Frontiers in Veterinary Science, 2024)
One of the principal limitations on livestock productivity in sub-Saharan Africa is the constraining effect of infectious diseases, including tick-borne blood pathogens. Currently, diagnostic markers for these pathogens are species or genus specific, making it challenging to implement high-throughput screening methods. The aim of this study was to develop and validate a novel high-throughput diagnostic tool capable of detecting a range of important haemopathogens in livestock. To achieve this, we developed a high-throughput diagnostic tool that can detect all species of Anaplasma, Ehrlichia, Theileria and Babesia present in a sample. The approach involves targeting the 16S/18S rDNA region by PCR and subjecting amplicons to deep sequencing, which allows for the identification of species present in a sample, and the exploration of haemopathogen communities. To validate the accuracy of this Next Generation Sequencing method, we compared the amplicon sequencing results with species-specific PCR and reverse line blot (RLB) test data of both control and field samples. The Haemabiome tool demonstrated the successful resolution of positive and negative samples, and highlighted the power of this diagnostic tool in identifying multiplicity of infections. The Haemabiome tool can therefore generate valuable insights regarding the understanding of the true diversity of species composition and the distribution of pathogen communities in field samples.